Mechanistic study of the Ni-catalyzed hydroalkylation of 1,3-dienes The origins of regio- and enantioselectivities and a further rational design - Bai, Yuna (Journal of computational chemistry, 2024)
© 2023 Wiley Periodicals LLC.